A submersible power station: part B propulsion systems - Serna, Jon; Romero, Stefania; Anselmi Palma, Eduardo; Fouflias, Dimitrios; Pilidis, Pericles (MDPI, 2025)
Nuclear power continues to be a great promise in the green revolution, as it is a cost-effective, low-emission, and safer alternative to fossil fuels that is capable of continuous operation. A preliminary design evaluation is presented for a submersible nuclear power station capable of operating under its own power during emergencies and routine maintenance. Because it is stationed at sea, it offers a resilient solution to natural disasters such as earthquakes and tsunamis, giving it the capability to disengage and sail to deeper waters in less than a half of an hour. In the present evaluation, the hull dimensions of a very large existing submarine and the turbomachinery layout of a Pebble Bed Modular Reactor cycle were used as baselines. The conceptual design of the submersible nuclear power station includes reactor and turbomachinery integration, preliminary sizing (4 pressure hull design; total length of 57.74 m), and propulsion system analysis, demonstrating the technical viability of the proposed submersible power station.
This article belongs to the Section Ocean Engineering
Keywords: 40 Engineering; 3005 Fisheries sciences; 3709 Physical geography and environmental geoscience; 4015 Maritime engineering; nuclear; submarine; hull; electric; power; propeller